Pemetaan informasi sebaran bidang ilmu pada tesis mahasiswa Sekolah Pascasarjana IPB University Tahun 2019-2020 - Ratnaningsih; Azizah; Fery Siswadi (Jurnal Pustakawan Indonesia, 2022)
Introduction. IPB University has produced many innovations both in research and scientific works that have been carried out by lecturers and students. As one of the requirements in completing their studies at university, students are required to write a scientific work in the form of a thesis. Method. This study uses descriptive quantitative research methods. The sample is limited to years from 2019-2020. The data was processed using MS Excel and the Universal Decimal Classification standard and mapping using the VosViewer-Visualizing Scientific Landscapes 1.6.1.5. Keyword analysis was carried out to obtain a visualization of the map of the relationship between keywords. Research result. The results showed that the thesis of IPB University students graduated from 2019-2020 as 1867 titles. The distribution of research by IPB University Masters students during the 2019-2020 main field group was mostly in class 600, namely the fields of applied sciences, medicine, and technology as many as 834 (44.6%). The co-word mapping on keywords in the postgraduate thesis research of IPB in 2019-2020 obtained as 7603 keywords with a limit of occurrence of at least 5 times divided into 12 clusters consisting of 144 items, 364 links, and 433 total link strength.